Isolation of Crude Oil from Polluted Waters Using Biosurfactants Pseudomonas Bacteria: Assessment of Bacteria Concentration Effects - Khalifeh, A.; Roozbehani, B.; Moradi, A. M.; Imani Moqadam, S.; Mirdrikvand, M. (Engineering, Technology & Applied Science Research, 2013)
Biological decomposition techniques and isolation of environmental pollutions using biosurfactants bacteria are effective methods of environmental protection. Surfactants are amphiphilic compounds that are produced by local microorganisms and are able to reduce the surface and the stresses between surfaces. As a result, they will increase solubility, biological activity, and environmental decomposition of organic compounds. This study analyzes the effects of biosurfactants on crude oil recovery and its isolation using pseudomonas sea bacteria species. Preparation of biosurfactants was done in glass flasks and laboratory conditions. Experiments were carried out to obtain the best concentration of biosurfactants for isolating oil from water and destroying oil-in-water or water-in-oil emulsions in two pH ranges and four saline solutions of different concentrations. The most effective results were gained when a concentration of 0.1% biosurfactants was applied.